Gute Praxisbeispiele kompakter und zugleich lärmarmer städtischer Quartiere. Abschlussbericht. - Preuß, Thomas; Bunzel, Arno; Hanke, Stefanie; Michalski, Daniela; Pichl, Josefine; Steinrücke, Elena; Janßen, Antje; Riemer, Evelyn (My University, 2020)
Die Umsetzung des Leitbilds der kompakten sowie nutzungsgemischten Stadt stellt besondere Anforderungen an ein ruhiges Wohnen bei gleichzeitig guter Aufenthaltsqualität im Freiraum neuer Quartiere im Rahmen der Innenentwicklung. Häufig sind die Standorte neuer Quartiere durch unterschiedliche Lärmquellen (Gewerbe-, Verkehrs-, Freizeit- und Sportlärm) vorbelastet. In der Publikation werden anhand von acht Fallstudien in deutschen Kommunen Lösungswege aufgezeigt, wie in der Praxis verdichtete, funktionsgemischte und dabei zugleich lärmarme Stadtquartiere geplant und realisiert werden können. So sind u.a. strategische Bausteine für die Realisierung kompakter und lärmarmer Quartiere beschrieben sowie die Instrumente und Maßnahmen für deren Umsetzung ausgeführt. Anhand der Beschreibung der acht Fallstudien über neue kompakte und zugleich lärmarme Quartiere werden diese ausführlich dargestellt. Schließlich werden zahlreiche lärmartenübergreifende und lärmartenspezifische Handlungsempfehlungen für Kommunen sowie Bund und Länder gegeben.

Implementing the model of a compact, mixed-use city poses specific challenges when it comes to designing quiet residential areas with high-quality open spaces in new districts as part of inner-city development. Often, the sites where new districts are planned are at a disadvantage on account of being impacted by various sources of noise – from commerce/industry, traffic, recreational activities and sports facilities. The publication looks at eight case studies from different German local authorities in order to flag up those solutions which available for planning and developing compact, mixed-function and low-noise urban districts. They demonstrate how conflicts between existing sources of noise – such as commercial enterprises, road and rail transport, and encroaching housing development – can be resolved at the legally binding land-use planning stage. First, there are various urban development and structural measures which can be implemented, for instance structures which shield buildings from noise sources, the allocation of noise-sensitive or -intensive uses, regulations pertaining to layout and structural/architectural measures. Second, provision is in practice made for both noise-protection measures at source and noise-avoidance actions. Amongst other things, the publication describes strategic building blocks for creating compact, low-noise districts as well as the instruments and measures for implementing those building blocks. These are presented in detail based on a description of the eight case studies of new compact, low-noise districts. Finally, numerous recommendations regarding specific types of noise as well as noise in general are made for local authorities, the federal government and federal states.
Keywords: Stadtquartier; Verdichtungsraum; Innenentwicklung; Lärmbelastung; Umgebungslärm; Lärmminderung; Lärmschutzmaßnahme; Planungsinstrument; Fallstudie; Städtevergleich; Handlungsempfehlung; Best Practice